Menata dan Mendisiplinkan “Yang Sosial” - Hasrul Hanif (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
This paper is a short version of the preliminary report for the sake of academic research under the supervision of Cornelis Lay. This paper is the political sociology studies to try the understanding how the dynamics of the relationship the orientation character of the political regime is a pattern or design scheme of social welfare policies that exists in Indonesia. The discussion paper sees on: what is the extention of practiclity of citizenship (citizenship) patterning with further understanding of the pattern relationship both the state and the citizen in the design of the existing social welfare.